The threat of MediaCorp to MediaWorks - Boo, Rosalind Gek Peng (2008)
This project explores the competition between MediaCorp Tv and MediaWorks. This project studies the types of programmes preferred by viewers and work out a Tv schedule for MediaWorks; both channel U and Channel i (formally known as Tv Works).